Report on the excavation of the Roman cemetary at Ospringe, Kent - Whiting, W. (Reports of the Research Committee of the Society of Antiquaries of London, 1931)
This is an account of the excavations of a Roman cemetery at Ospringe in Kent, England, undertaken in 1921. Included are descriptions of artefacts such as pottery and human remains, together with an account of the methodology used to unearth these.